(untitled) (Journal of Civil Engineering Researchers, 2022)
Today, wind energy is considered as one of the most used types of renewable energy for electricity production. Over the past two decades, wind energy has been a major source of electricity, and electricity supply has been drastically increasing. Among the technologies available to generate electricity from wind, wind turbines play a major role, with offshore wind turbines playing a significant part. Offshore structures such as wind turbines, unlike other types of structures, are in a dynamic environment, the main forces generating this dynamic wave and wind environment, which impose significant structural vibrations, fatigue loads and significant loads on the blades, the turbine, structural platform, and other components import it. Welded joints and points in offshore structures are vulnerable to fatigue failure due to stress concentrations and intermittent environmental loading. Offshore structures have been exposed to shock forces and cyclic loads throughout their lifetimes, which cause the cyclic loads to cause fatigue in the joints. The dynamic forces of the waves gradually cause small cracks in the structural joints over time, and the expansion of these cracks at the weld foot and joints of the structural members reduces the overall stiffness of the joint and in some cases even removes the member from the location of connection. Much research has been done on the use of offshore wind energy, but despite the special attention of the worldwide scientific community on offshore wind energy extraction, there are still few studies domestically. Considering the water levels in the south of Iran and the platforms in the area will add to the importance of this study. The turbine structure will be examined to perform the research by using and inspiring DNV and API by-laws when the method is nonlinear. The case study will also cover the Strait of Hormuz and the time zone. This research is carried out using coding in Matlab as well as analysis in Bentley SACS finite element software which is dedicated to the design of offshore steel structures. The results indicate that the presence of the turbine blade geometry has a significant effect on the fatigue life of the retaining structure and the entire structure.